Two Major Fungal Diseases of Rice (Oryza sativa L.) and Management Methods: Review: Two Major Fungal Diseases of Rice (Oryza sativa L.) and Management Methods: Review - Admasu, Solomon (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2020)
Rice blast and sheath blight disease caused by a fungus Pyricularia oryzae (Cavara) and Rhizoctonia solani, respectively, is a worldwide problem in rice and is dangerous because of its yield loss potential up to 100%. The objective of this review is to provide useful facts about rice blast and sheath blight disease and to be familiar with the different methods for controlling the diseases. Rice blast and sheath blight disease has been recognized in more than 85 rice producing countries worldwide. At present, more than 100 R genes for blast resistance have been identified in rice. Unlikely, there is no commercial variety which is resistant to sheath blight disease, but the land races can be used to achieve the novel genes for disease resistance. Rice sheath blight caused by R. solani is a destructive disease that leads to yield loss of 20–50%. Sheath blight disease management is difficult because of high genetic diversity of the causal organism and wide host range. Symptoms of this disease are generally observed from the milking stage to tillering stage of the rice crop. P. oryzae is favored by moist warm conditions and increased by fog, shade, or frequent light rains. Similarly, rice cultivar that accumulated more silicon on the shoots showed less incidence of rice blast. Among the fungal disease control method may include biological, chemical, and nutrient management; cultural practices and use of resistant varieties are the best disease management options.